Determination of Acrylamide Using Ruthenium Dioxide Modified Carbon Paste Electrode - Červenka Libor; Žabčíková Simona; Křivská Lenka (My University, 2015)
A simple indirect method for acrylamide determination using a carbon paste electrode (CPE) modified with powdered ruthenium dioxide is described in the study. The voltammetric response of RuO2/CPE in a 1.0 M LiCl supporting electrolyte resulted in the reduction current at a potential of 1.03 V vs. Ag/AgCl/3.0 M KCl due to the formation of unspecified Ru-Cl species. The addition of acrylamide decreased the reduction current at 1.03 V, giving rise to a linear response in the concentration range from 0.25 uM to 1.5 uM with a limit of detection found to be 0.94 uM. The method developed was successfully applied to analyse potato crisps sample with a recovery rate of 97.9 %.
Stanovení akrylamidu uhlíkovou pastovou elektrodou modifikovanou oxidem ruteničitým
Keywords: acrylamide; ruthenium dioxide; carbon paste; voltammetry; akrylamid; oxid ruteničitý; uhlíková pasta; voltametrie